Structural and electronic properties of medium-sized beryllium doped magnesium BeMgn clusters and their anions - Zhao, Yaru; Xu, Yuqing; Chen, Peng; Yuan, Yuquan; Qian, Yu; Li, Qiao (Results in physics, 2021)
•The structural search of the global minimum for neutral and anionic Mgn and BeMgn clusters are performed by utilizing efficient CALYPSO code with subsequent DFT at B3PW91 and PBE0 level.•The most stable isomers for different cluster size are confirmed in light of their total energies and PES spectra.•All of the most stable structures of BeMgn0/− clusters are filled cage-like frameworks.•The D4d of high symmetric BeMg16 caged structure with one centered Be atom has robust stability. Bimetallic clusters have attracted much attention because of the structural and property changes that occur: cluster size and doping. Here, we performed a structural search of the global minimum for bimetallic BeMgn0/− (n = 10–20) clusters by utilizing efficient CALYPSO structural searching program with subsequent DFT calculations. A large number of low energetic isomers converge and the most stable structures are confirmed by comparing the total energies for different cluster sizes. Satisfactory agreement between theoretical and experimental PES spectra demonstrates the validity of our predicted global minimum structures. It is found that the most stable structures of BeMgn0/− clusters are filled cage-like frameworks at n = 10–20. The localized position of Be atoms changes from completely encapsulated sites to surface sites, after which the position reverts to the caged Mg motif. In all BeMgn0/− clusters, the charge transfers from the Mgn motif to Be atoms. Increasing occupations of p orbitals manifest their increasing metallic behaviors. A stability analysis revealed that the D4d symmetric BeMg16 caged structure with one centred Be atom has robust stability, which can be because BeMg16 possesses a closed electronic shell of 1S21P61D101F42S21F10 filled with 34 valence electrons and strong Be-Mg bonds due to s-p hybridization. This finding is supported by multi-centre bonds and Mayer bond order analyses.